Economic advantage of sourcing certified sweetpotato planting materials from low to high disease pressure areas versus in situ multiplication at the latter - Kwikiriza, N.; Namanda, S.; Zziwa, S.; Kyalo, G.; McEwan, M.; Low, J.W.; Rajendran, S.; Mwanga, R.O.M. (2025)
Sweetpotato (Ipomoea batatas (L.) Lam.) is a major staple crop in Uganda, with average on-farm yields of 4.2 t ha-1, far below the potential 25 t ha-1 on-station and under rain-fed conditions. Low productivity is attributed partly to limited access to affordable disease-free planting material, especially in high sweetpotato (SP) virus disease (SPVD) areas. Vine multiplication is more viable in low-SPVD zones, where previous cropped fields as the main sources of cross-infection dry up during prolonged dry periods. The objective of this study was to investigate the economic advantage of multiplying diseasefree planting materials from the low-disease pressure areas in central Uganda and supplying them to high-diseased pressure areas in northern Uganda, compared to multiplying the materials in situ in the latter areas. A field survey was conducted in central and northern Uganda, areas known to be low and high in SPVD pressure, respectively. Results showed that vine multiplication in the low-SPVD areas incurred a cost of US$ 1.8 per bag of 1,000 of disease-free cuttings, compared to US$ 2.5 in high-SPVD areas, with profit margins up to 30% higher in low-SPVD areas. Although the cost of production per unit of vines was lower in the low SPVD pressure areas, sourcing disease free vines and subsequent transportation to high SPVD endemic areas, was not economically feasible due to high multiple transport costs. In situ multiplication in high SPVD pressure areas was the most cost effective since beyond 300 Km from the source, the transportation costs became prohibitive. From this study, it is recommended that disease free seed production in high SPVD areas should be strengthened to achieve self-sufficiency and sustainable vine production.